Assessing genetic diversity for a pre-breeding program in Piaractus mesopotamicus by SNPs and SSRs - Mastrochirico-Filho, Vito Antonio (2019)
Fil: Fil: Mastrochirico-Filho, Vito Antonio. São Paulo State University (Unesp). Unesp's Aquaculture Center (Caunesp); Brazil.